2015
DOI: 10.1037/spq0000093
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among Taiwanese adolescents’ perceived classroom environment, academic coping, and burnout.

Abstract: Although academic pressures are regarded as a primary source of stress among students in Asian countries, there has been paucity of research on the effects of classroom settings providing structure and peer support on Asian adolescents' use of coping strategies and academic burnout. The present study was intended to address this issue. Three hundred seventy-four 8th Grade Taiwanese students completed a self-reported survey that assessed their perceived classroom structure along with peer support, academic copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
2
24
0
2
Order By: Relevance
“…These results build on evidence from prior research in two ways. First, our findings suggest that in addition to shaping students' academic engagement (Estell et al, 2002;Gest et al, 2008;Kindermann, 2007;Ryan, 2001;Vollet et al, 2017) and coping (Reschly et al, 2008;Shih, 2015), peers also contribute to students' propensity to re-engage following academic setbacks through mechanisms of influence that occur through frequent interaction. This study did not explicitly examine mechanisms of influence; however, many can be imagined.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results build on evidence from prior research in two ways. First, our findings suggest that in addition to shaping students' academic engagement (Estell et al, 2002;Gest et al, 2008;Kindermann, 2007;Ryan, 2001;Vollet et al, 2017) and coping (Reschly et al, 2008;Shih, 2015), peers also contribute to students' propensity to re-engage following academic setbacks through mechanisms of influence that occur through frequent interaction. This study did not explicitly examine mechanisms of influence; however, many can be imagined.…”
Section: Discussionmentioning
confidence: 89%
“…To date, no research has directly examined the links between peers' and students' re-engagement and how these links may be facilitated through frequent interactions. However, related bodies of research have shown that peers play a central role in shaping students' academic engagement (Altermatt & Pomerantz, 2003;Kindermann, 1993Kindermann, , 2007Ryan, 2001;Shin & Ryan, 2014;Vollet et al, 2017), academic coping (Reschly, Huebner, Appleton, & Antaramian, 2008;Shih, 2015), self-efficacy (Schunk & Hanson, 1985), and achievement (Rambaran et al, 2017;Shin & Ryan, 2014), through mechanisms of influence (e.g., modeling, reinforcement, social comparison) that play out within frequent interactions.…”
Section: Current Studymentioning
confidence: 99%
“…This result was consistent with Lee’s (2009) findings. It is plausible that the higher proportion of Korean students categorized as High and Mid MA stems from their greater pressure to do well on examinations, as a study by Tan and Yates (2011) revealed. Furthermore, there is an interesting finding that American students demonstrated a bit higher prevalence of High MA compared to the Korean students after the MLPA classification, while the American sample reported significantly lower levels of MA than Korean sample on the overall country level.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in relation to mental health, the symptoms evaluated as somatizations, obsessions and compulsions, interpersonal sensiti- 14 . This decrease could be explained from the socio-family support and even from the support of classmates, conditions that influence mental health but can do so from its role in the academic burnout experience containing its severity and increasing the commitment to face the academic challenges 47,48 .…”
Section: Discussionmentioning
confidence: 99%